Getting to know the deep web: an initial approach to minimizing IT risks in academic environments - Vitola-Quintero, Marena; Mendoza-Pérez, Cristhian; Rosero-Castro, Angie; Romero-Duarte, Jenny (EFIM Ediciones, 2020)
This work is the result of a search and compilation of information related to the Deep Web or Deep Web, which refers to a small part of the network that contains material, information and web pages not indexed in search engines such as Google, Bing and Yahoo. From the opinion expressed by Gay (2015) it is important to highlight that “The Deep Web is a hidden internet space where the frst guarantee is anonymity”. This guarantee serves to house a vast network of illegal services, such as drug trafcking, white trafcking, hiring of hitmen, passport purchase and bank accounts, among other crimes, also allows political activists living in dictatorial countries to share sensitive information with the rest of the world and a lot of information classifed by countries like the United States, however, it also oﬀers the possibility of accessing diverse academic content that can be useful when building a document of this nature; in that order of ideas the objective of the present investigation was to carry out a descriptive study gathering documentary information about the risks and threats associated with the Deep Web, to generate an initial approach to the subject by the crew of the Naval School of Cadets “ Admiral Padilla ”, avoiding future possible risks associated with information leaks due to ignorance and inappropriate use of the deep internet. The most important characteristics of the object of study with respect to its appearance and behavior over time were addressed.